Waterborne acrylic varnishes durability on wood surfaces for exterior exposure - Custódio, J. (2010)
The protection performance of varnishes applied to two different wooden substrates (maritime pine and iroko) for outdoor exposure was investigated for eight different varnish systems (with and without colorants and two different light stabilizers). All were subjected to accelerated artificial weathering and natural weathering. Several test methods were used to evaluate the appearance and physical-chemical properties of the coatings during the degradation. The results obtained lead to the selection of the best varnish formulation for the protection of wood for exterior use and provide useful evaluation of the test methods employed.